Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.
Trending News
Find a polar form, z=re^iθ, of the complex number z=-6+2 sqrt 3 i. Use exact values?
4 Answers
- la consoleLv 72 years ago
Recall:
z = a + ib ← this is a complex number
m = √(a² + b²) ← this is its modulus
tan(α) = b/a → then you can deduce α ← this is the argument
In your case:
z = - 6 + 2i√3 ← you can see that: a = - 6 and you can see that: b = 2√3
m = √[(- 6)² + (2√3)²]
m = √[36 + 12]
m = √48
m = 4√3 ← this is the modulus of z
tan(α) = b/a
tan(α) = (2√3)/- 6
tan(α) = - (√3)/3
α = π - (π/6)
α = 5π/6
z = (4π3).e^[(5π/6).i]
- 2 years ago
z = r * e^(i * t)
z = r * (cos(t) + i * sin(t))
z = r * cos(t) + r * sin(t) * i
z = -6 + 2 * sqrt(3) * i
r * cos(t) = -6
r * sin(t) = 2 * sqrt(3)
r^2 * cos(t)^2 = 36
r^2 * sin(t)^2 = 4 * 3 = 12
r^2 * cos(t)^2 + r^2 * sin(t)^2 = 36 + 12
r^2 * (cos(t)^2 + sin(t)^2) = 48
r^2 * 1 = 48
r = sqrt(48)
r = sqrt(16 * 3)
r = -4 * sqrt(3) , 4 * sqrt(3)
Let's assume a positive value for r (we'll do the negative value later)
r * cos(t) = -6
4 * sqrt(3) * cos(t) = -6
cos(t) = -6 / (4 * sqrt(3))
cos(t) = -6 * sqrt(3) / (4 * 3)
cos(t) = -6 * sqrt(3) / 12
cos(t) = -sqrt(3) / 2
t = 5pi/6 , 7pi/6
4 * sqrt(3) * sin(t) = 2 * sqrt(3)
sin(t) = 1/2
t = pi/6 , 5pi/6
5pi/6 is the common value of t
4 * sqrt(3) * (cos(5pi/6) + i * sin(5pi/6)) =>
4 * sqrt(3) * e^((5pi/6) * i)
Using a negative value for r
-4 * sqrt(3) * cos(t) = -6
cos(t) = sqrt(3)/2
t = pi/6 , 11pi/6
-4 * sqrt(3) * sin(t) = 2 * sqrt(3)
sin(t) = -1/2
t = 7pi/6 , 11pi/6
t = 11pi/6
z = -4 * sqrt(3) * e^((11pi/6) * i)
Hopefully you can see the symmetry here. By multiplying r by -1, our angle is out by pi radians or 180 degrees.
- Φ² = Φ+1Lv 72 years ago
z = -6 + 2 sqrt 3 i
z = √((-6)² + (2 sqrt 3)²) (-6 + 2 sqrt 3 i) / √((-6)² + (2 sqrt 3)²)
z = 4√3 (-6 + 2 sqrt 3 i) / (4√3)
z = 4√3 (-√3/2 + 1/2 i)
z = 4√3 cis(5π/6)
z = 4√3 e^(i 5π/6)